INTERNALIZATION OF PANCASILA VALUES BASED ON LOCAL WISDOM"JARANAN TURANGGA YAKSA"IN ELEMENTARY SCHOOL - Atika Mayasari; Sri Marmoah; Tri Murwaningsih (JURNAL PENDIDIKAN DASAR, 2021)
Abstract:  The purpose of this study was to determine the value of Pancasila contained in the local wisdom of Jaranan Turangga Yaksa and to describe the internalization of the values of Pancasila and the local wisdom of Jaranan Turangga Yaksa in elementary schools and to find out the obstacles and solutions to internalizing the values of Pancasila based on local wisdom of Jaranan Turangga Yaksa. The research will be carried out at SD Negeri 3 Ngantru, Trenggalek District, Trenggalek Regency, East Java by using a form of qualitative research with the intention of describing the activities of implementing character values through local wisdom in these elementary schools and the method used in this research is descriptive research method. The results of the research that have been carried out are the values of Pancasila which are contained in the local wisdom of Jaranan Turangga Yaksa starting from the first precept, namely the almighty deity where the art of Jaranan Turangga aims to give alms from the community to God Almighty by giving crops to people in need. . The second Pancasila value contained in the local wisdom of Jaranan Turangga Yaksa, namely the emergence of a sense of tolerance, friendship, social care, an attitude of love for peace among humans and also the application of the fifth Pancasila precept, namely social justice for all Indonesian people. Keywords: Internalilation, Pancasila Values, Local Wisdom, Jaranan TuranggaYaksa